2011
DOI: 10.1063/1.3560911
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of magneto-Rayleigh–Taylor instability growth during the implosion of initially solid metal liners

Abstract: A recent publication [D. B. Sinars et al., Phys. Rev. Lett. 105, 185001 (2010)] describes the first controlled experiments measuring the growth of the magneto-Rayleigh–Taylor instability in fast (∼100 ns) Z-pinch plasmas formed from initially solid aluminum tubes (liners). Sinusoidal perturbations on the surface of these liners with wavelengths of 25–400 μm were used to seed single-mode instabilities. The evolution of the outer liner surface was captured using multiframe 6.151 keV radiography. The initial pape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(53 citation statements)
references
References 24 publications
4
48
0
1
Order By: Relevance
“…As discussed above, the beryllium liners shown in red have an aspect ratio, A R ¼ R out /DR ¼ 6 for all simulations presented in this study. Numerical simulations 4 indicated and experiments [7][8][9][10][11] have confirmed that A R ¼ 6 liners should be sufficiently robust to the RT instability. These experiments were performed with drive currents of approximately 18 MA.…”
Section: Numerical Model Of Maglif Implosionsmentioning
confidence: 99%
See 1 more Smart Citation
“…As discussed above, the beryllium liners shown in red have an aspect ratio, A R ¼ R out /DR ¼ 6 for all simulations presented in this study. Numerical simulations 4 indicated and experiments [7][8][9][10][11] have confirmed that A R ¼ 6 liners should be sufficiently robust to the RT instability. These experiments were performed with drive currents of approximately 18 MA.…”
Section: Numerical Model Of Maglif Implosionsmentioning
confidence: 99%
“…The fuel preheating and the magnetically inhibited radial conduction reduce the required volume compression and thus the convergence needed to achieve fusion temperatures. Numerical simulations and experiments 4,[7][8][9][10][11] indicate thick walled liners with an aspect ratio (A R ¼ R outer /DR wall $ 6) should be adequately robust. Larger aspect ratios may be possible with the suppression of the electro-thermal instability, 12 but we use the conservative value A R ¼ 6 for this study.…”
Section: Introductionmentioning
confidence: 99%
“…Ref. 31). Detailed consideration of these processes is beyond the scope of our present study, and will be a subject of future investigations.…”
Section: Potential Development Of Rayleigh-taylor Instabilitiesmentioning
confidence: 99%
“…The amplitude of the 400-mm-wavelength mode as a function of time was compared with the simulations as well, as shown in the plot in Figure 5. Additional data along with far more detailed comparisons between the simulations and experiments are described in two of our publications [6,7]. Comparisons between these data and several simulation tools used in the ICF and HEDP complex are ongoing, including LASNEX, GORGON, ALEGRA, HYDRA, KULL, and ARES.…”
Section: Single-mode Magneto-rayleigh-taylor Experimentsmentioning
confidence: 99%
“…Thus, the main thrust of this LDRD proposal was to study the key physics issue of liner stability. These experiments were extremely successful and resulted in several high-profile publications [6,7,8,9,10,11,12]. The results of these studies are summarized in Section 2.…”
Section: Introductionmentioning
confidence: 99%